Is neuralgia a transcriptional channelopathy? (2010)
Neuralgia, is a symptom of some neurological disorders and can be found at any age. It is characterized by paroxysmal and lancinating pain that follows the path of the affected nerve. It can be spontaneous or may be triggered by any type of stimuli. This pain is usually brief but may be severe, pain-free intervals being common. This symptom is the main characteristic of some neurological entities and, due to its presence and importance, these diseases are thereby known as trigeminal neuralgia, glossopharyngeal neuralgia or postherpetic neuralgia. Neuralgia is caused by irritation or nerve damage arising from inflammation, trauma, surgery, compression by adjacent structures such as tumors, infection and chemical or physical irritation of a nerve, even though the cause remains unknown in most cases. This chapter presents the evidence sustaining the hypothesis that neuralgia is a clinical expression of a transcriptional channelopathy. This will help (in the near future) in designing new drugs orientated towards such target and lead to advances in diagnosing and treating patients who are affected by this important symptom. © 2010 by Nova Science Publishers, Inc.